Dynamic influences of power on trust: Changes in power affect trust in others. Issue 1 (2nd January 2019) - Brion, Sebastien; Mo, Ruo; Lount, Robert B.
ABSTRACT: Though much research has examined the trust development process, we know little about how changes in one's power impact trust development. Building on relevant literatures, we propose that independent of one's absolute power, trust increases (or decreases) as a function of how much power individuals gain (or lose) over time. We find support for our hypotheses in a multisource nine-month longitudinal study of individuals working in teams. Mediation analyses, moreover, demonstrate that changes in the perceptions of others' trustworthiness help explain the positive relationship between power change and trust. Our findings contribute to the literatures on trust and power by highlighting the crucial role that power dynamics play in generating downstream trust. We discuss theoretical implications for research on power and trust, as well as practical implications for managing trust within teams.